Competing Through Quality - Yahya, Salleh; Mohd. Salleh, Lailawati; Goh , Wee Keat (Asian Academy of Management (AAM), 2001)
This paper provides information on the following quality practices in a Malaysian context: (1) general quality status, (2) application of quality tools and techniques, (3) implementation of TQM, (4) certification of ISO 9000, (5) practices of quality costing and (6) critical success factors of quality efforts. Cross-sectional data of 405 Malaysian companies is collected and analysed. Based on the results, a Quality Development Model designated for the implementation of a quality programme is formulated. This model comprises of four continuous improvement stages, namely: ( 1 ) assessment, (2) development, (3) deployment, and. (4) review.